Multisensor fusion for acquisition of the profile of surfaces - Fonseca, Jaime C. (2004)
This paper presents multisensor fusion techniques for the acquisition of the profile of surfaces with minimum error using low cost sensors ultrasonic sensors. These surfaces are composed by areas with different depths, corners and specular surfaces. To minimize the constraints of sonar sensors, it was developed dedicated software and hardware, as well as an empirical model was obtained from real data. This model is based in two proposed concepts: Points of Constant Depth (PCD) and Areas of Constant Depth (ACD). Having this sonar model in mind, four multisensor fusion techniques are used separately to validate the PCDs and decide the ACDs: average and variance, fuzzy controller and heuristic method based in rules. In this work a PUMA 560 manipulator was equipped with a CCD video camera and four ultrasonic sensors on the wrist, to acquire data for internally representation of the geometry of the part’s surface, exploiting the mobility of the robot. The CCD camera view defines the working area while the ultrasonic sensors enable the acquisition of the surface profile.